Anisochilus carnosus leaf extract mediated synthesis of zinc oxide nanoparticles for antibacterial and photocatalytic activities. (November 2015) - Anbuvannan, M.; Ramesh, M.; Viruthagiri, G.; Shanmugam, N.; Kannadasan, N.
Abstract: We describe a simple combination reaction between zinc nitrate and leaf extract of Anisochilus carnosus to prepare ZnO nanoparticles. The synthesized NPs subjected to structural, optical, and morphological analyses. The structural analysis demonstrates that the prepared ZnO NPs are crystalline and exhibit hexagonal wurtzite structure. Further, the photocatalytic performance of the ZnO tested against the methylene blue (MB) dye under UV radiation has significant photodegradation. The antibacterial activities of the prepared products analyzed against some selected human pathogens showed excellent results.